Pengaruh Kepemilikan Investor Institusi Asing Terhadap Volatilitas Harga Saham di Indeks Kompas100 - Muhamad Farhan; Sung Suk Kim (Politeknik Ganesha Medan, 2023)
This journal investigates the effect of foreign institutional investor ownership on share price volatility with a sample of 207 companies between 2008 and 2021 that are included in the Kompas100 Index. The empirical results of this study indicate that foreign institutional investor ownership reduces share price volatility in Indonesia with control variables: market capitalization, turnover, leverage, and market to book. In addition, we also document the results of research that the greater the market capitalization of a company, the lower the volatility of its share price and foreign investors increase stock trading turnover in Indonesia because it attracts the attention of domestic investors, especially individual investors. Foreign institutional investors also prefer to invest in companies with a market to book rating that have a premium.